2014
DOI: 10.1097/mcp.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

Periostin, a novel biomarker of TH2-driven asthma

Abstract: Emerging data suggest a role for periostin in refining asthma phenotypes and predicting the response to targeted therapy. Although early data are promising, further investigations are needed to confirm these findings and to identify other clinical applications in which periostin may be valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 49 publications
2
54
0
4
Order By: Relevance
“…Nowadays, it is well recognized that the thickening of the epithelial-connective tissue interface in asthma is the consequence of excessive deposits of collagen types I, III, and V, associated to fibronectin and tenascin-C. Periostin identification in the same location as these extracellular matrix protein supports the assertion that they represent different components of the bronchial subepithelial fibrosis [9,16]. These initial observations have been later completed by other studies which revealed an increased periostin serum or sputum level in patients with allergic bronchial asthma [12,17,18]. Thus, an increased periostin level associated with eosinophilia and Th2 mediated inflammation is seen in a specific type of bronchial asthma.…”
Section: Periostin and Bronchial Asthmasupporting
confidence: 59%
“…Nowadays, it is well recognized that the thickening of the epithelial-connective tissue interface in asthma is the consequence of excessive deposits of collagen types I, III, and V, associated to fibronectin and tenascin-C. Periostin identification in the same location as these extracellular matrix protein supports the assertion that they represent different components of the bronchial subepithelial fibrosis [9,16]. These initial observations have been later completed by other studies which revealed an increased periostin serum or sputum level in patients with allergic bronchial asthma [12,17,18]. Thus, an increased periostin level associated with eosinophilia and Th2 mediated inflammation is seen in a specific type of bronchial asthma.…”
Section: Periostin and Bronchial Asthmasupporting
confidence: 59%
“…Periostin clearly plays crucial roles in tissue repair. However, in some cases, chronic or superabundant periostin expression can accelerate pathogenesis of tumours (22,23), bronchial asthma (24,25), atopic dermatitis (26,27), polycystic kidney disease, and other fibrotic diseases (28). As recently reported, periostin promotes chronic inflammation by activating nuclear factor kappa B (NF-ĸB) signaling (26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…There was also no difference between periostin values of women in early pregnancy (first and second trimester) and women in late pregnancy (third trimester) neither in the AP nor in the HP group (p > 0.05). ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 13 We could not detect any association between periostin, CRP or IL-6 levels and obstetrical data such as gestational age at delivery and fetal birth weight.…”
Section: Relationship Of Inflammatory and Functional Parameters To Obmentioning
confidence: 42%
“…In the recent years, periostin has emerged as a valuable biomarker in asthma, primarily in its T helper 2 (Th2)-induced, eosinophil-predominant phenotype [13]. Periostin is an extracellular matrix protein, which is expressed at low levels in connective tissue and plays a role in generation of collagen.…”
Section: Introductionmentioning
confidence: 99%